The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1016/j.jpeds.2017.10.052
|View full text |Cite|
|
Sign up to set email alerts
|

Divergent Patterns of Mitochondrial and Nuclear Ancestry Are Associated with the Risk for Preterm Birth

Abstract: Objective To examine linkages between mitochondrial genetics and preterm birth by assessing the risk for preterm birth associated with the inheritance of nuclear haplotypes that are ancestrally distinct from mitochondrial haplogroup. Study design Genome-wide genotyping studies of cohorts of preterm and term individuals were evaluated. We determined the mitochondrial haplogroup and nuclear ancestry for individuals and developed a scoring for the degree to which mitochondrial ancestry is divergent from nuclear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 36 publications
0
14
1
Order By: Relevance
“…In previous studies, we and others have reported that mitochondrial dysfunction and other metabolic abnormalities in the placenta are linked to SPTB in the human ( Zhang et al, 2010 ; Crawford et al, 2018 ; Martin et al, 2018 ; Elshenawy et al, 2020 ). Consistent with these previous findings, IPA canonical pathway analysis revealed that intrauterine LPS treatment was associated with dysregulation of redox status/increased oxidative stress, and mitochondrial dysfunction in placenta ( Table 1 and Supplementary Table S4 ).…”
Section: Resultsmentioning
confidence: 85%
“…In previous studies, we and others have reported that mitochondrial dysfunction and other metabolic abnormalities in the placenta are linked to SPTB in the human ( Zhang et al, 2010 ; Crawford et al, 2018 ; Martin et al, 2018 ; Elshenawy et al, 2020 ). Consistent with these previous findings, IPA canonical pathway analysis revealed that intrauterine LPS treatment was associated with dysregulation of redox status/increased oxidative stress, and mitochondrial dysfunction in placenta ( Table 1 and Supplementary Table S4 ).…”
Section: Resultsmentioning
confidence: 85%
“…As mentioned above, one unique characteristic of the mitochondrial genomic system is the G x G interaction, or in other words, the interaction between factors encoded by the nuclear and mitochondrial genomes. The possible, and actual, impact of compatible vs. incompatible mito-nuclear genotypes were investigated in cell culture harboring different combinations of mtDNAs and nDNAs (cybrids) (Suissa et al, 2009;Gomez-Duran et al, 2010;Ji et al, 2012;Kenney et al, 2014;Crawford et al, 2018), and from repeated backcrossing of model organisms for the sake of generating animals with differential combinations of mito-nuclear genotypes (conplastic animals) originating from different strains of model organisms (Dingley et al, 2014;Latorre-Pellicer et al, 2016). Additionally, population genetics studies from species and different population isolates from the same species in the copepod Tigriopus californicus (Burton et al, 2006;Ellison and Burton, 2006), in reptiles (chameleons) ( Bar-Yaacov et al, 2015) and in birds (sparrows) (Trier et al, 2014), revealed hybrid incompatibility, which constitutes an important step toward speciation.…”
Section: Mito-nuclear Interactions: Corresponding Signatures Of Selecmentioning
confidence: 99%
“…More recently, Crawford et al. [56] examined whether the differences in the ancestral inheritance between mitochondrial and nuclear genome are associated with an increased risk of preterm birth, and they showed that infants with higher degrees of divergent ancestry were at increased risk of preterm birth. This finding may partially explain the increased risk of preterm birth in African American infants, and the mechanism may arise from the “mismatch” between haplogroup-defining mitochondrial polymorphisms with geographically local nuclear variation.…”
Section: Genomic Discoveriesmentioning
confidence: 99%